Efficacy and underlying mechanisms of acupuncture therapy for PTSD: evidence from animal and clinical studies - Tang, Xiaorong; Lin, Shumin; Fang, Danwei; Lin, Binjing; Yao, Lulu; Wang, Lin; Xu, Qin; Lu, Liming; Xu, Nenggui (Frontiers in Behavioral Neuroscience, 2023)
As a major public health problem, posttraumatic stress disorder (PTSD) has a substantial impact on individuals and society. The total excess economic burden of PTSD in the US is estimated to be more than $232.2 billion a year. Acupuncture is widely used in patients with PTSD, and an increasing number of studies have been undertaken to assess the efficacy and underlying mechanisms of acupuncture for the treatment of individuals with PTSD. However, there has not yet been a review that simultaneously elucidates the therapeutic efficacy and biological mechanisms of acupuncture. We wished to examine the efficacy and underlying mechanisms of acupuncture for the treatment of individuals with PTSD. We conducted this review in three sections: a meta-analysis, an acupoint analysis, and mechanism research. PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure Database (CNKI), WanFang Database, China Biology Medicine Database (CBM), Chinese Science and Technology Journals Database (VIP), and other databases were searched from January 1, 2012, to November 27, 2022. Based on the included studies, we first determined whether acupuncture is more effective than psychological treatment or pharmacological treatment for treating and improving the quality of life of individuals with PTSD by meta-analysis. Second, the most commonly used acupoints and parameters of acupuncture were summarized based on animal and clinical studies. Third, we attempt to summarize the current mechanisms of acupuncture in the treatment of PTSD. Finally, 56 acupoint analyses, eight meta-analyses, and 33 mechanistic studies were included. Acupuncture outperformed pharmacotherapy treatment in improving symptom scores by CAPS, HAMA, HAMD, PCL-C, and SCL-90 somatization for PTSD, and outperformed psychotherapy treatment in improving symptom scores by CAPS PCL-C and HAMD, according to the meta-analysis. GV20 was the most frequently used acupuncture point in clinical studies and animal studies, with a 78.6% application rate. Acupuncture may be effective in treating PTSD by regulating the structure and components of several brain areas, regulating the neuroendocrine system, and involving signalling pathways. In conclusion, this finding indicates that acupuncture has promising potential for treating PTSD.